Pre-Service EFL Teachers’ Digital Literacy and Factors Affecting Digital Literacy Development - Eryansyah Eryansyah; Ismail Petrus; Sri Indrawati; Ernalida Ernalida (Indonesian Research Journal in Education |IRJE|, 2020)
This study was intended to investigate pre-service EFL teachers’ digital literacy skills and factors affecting them in developing their digital literacy skills. Respondents participating in this research were the English Education Study Program students of a university in South Sumatra Province. They were in the fourth-year of study. Research data were collected through questionnaires. Research findings revealed that pre-service EFL teachers’ digital literacy was categorized above acceptable level. The main factors inhibiting them from developing digital literacy competence were a limited number of computers with online access on campus, no ICT training provided by the university for them, less practice of digital technology in teaching and learning activities, lack of budget to access the internet outside campus. Sustainable availability of digital resources at the campus, regular training of ICT on campus, and persistent integration of digital technologies in language learning seemed to be important develop their digital literacy skills.